2008
DOI: 10.1007/s12160-007-9002-y
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Adult Fruit and Vegetable Consumption in the National 5 A Day for Better Health Community Studies

Abstract: The present study findings provide strong support for mediation of F&V consumption by two variables: self-efficacy and knowledge. The authors discuss the findings in relation to study limitations and future research directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
5
15
0
Order By: Relevance
“…Our results replicate the mediating effects of self-efficacy on F&V intake and fat restriction found at 1-year follow-up [35] and extend these findings by suggesting that change in self-efficacy may play an important role in the durability of dietary gains. Our findings are also consistent with those of prior intervention trials that found support for the mediating effect of behaviorspecific self-efficacy on F&V intake in community-dwelling adults [40][41][42]. The present results in combination with prior research largely support the prediction derived from Social Cognitive Theory that confidence in one's ability to perform a behavior will play a critical role in health behavior change [33,34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results replicate the mediating effects of self-efficacy on F&V intake and fat restriction found at 1-year follow-up [35] and extend these findings by suggesting that change in self-efficacy may play an important role in the durability of dietary gains. Our findings are also consistent with those of prior intervention trials that found support for the mediating effect of behaviorspecific self-efficacy on F&V intake in community-dwelling adults [40][41][42]. The present results in combination with prior research largely support the prediction derived from Social Cognitive Theory that confidence in one's ability to perform a behavior will play a critical role in health behavior change [33,34].…”
Section: Discussionsupporting
confidence: 91%
“…Our results replicate the mediating effects of self‐efficacy on F&V intake and fat restriction found at 1‐year follow‐up and extend these findings by suggesting that change in self‐efficacy may play an important role in the durability of dietary gains. Our findings are also consistent with those of prior intervention trials that found support for the mediating effect of behavior‐specific self‐efficacy on F&V intake in community‐dwelling adults .…”
Section: Discussionsupporting
confidence: 90%
“…The clinical significance of this study is strongest in relation to the findings of participants' increased readiness to make changes to both F&V and fat intake, relative to controls. Many recent studies have shown that greater readiness to change relates directly to change in dietary behaviors (Campbell et al, 2008;Di Noia, Schinke, Prochaska, & Contento, 2006;Henry, Reimer, Smith, & Reicks, 2006;Nitzke et al, 2007;Robinson et al, 2008) and is often a first step toward making difficult behavioral changes. Thus, although we found only a modest increase in fruit and vegetable consumption, we posit that a program that increases participants' motivation is an important addition to the relatively sparse offerings in online nutrition education available to university students (Cousineau et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These studies resulted in significant improvements in fruit and vegetable consumption, with an average effect size of 0.3-0.5 servings of fruits and vegetables per day. Subsequent analyses of the 5-a-day studies conducted among adults demonstrated that improvements in knowledge and self-efficacy were significant mediators of the observed increases in fruit and vegetable intake (Campbell et al, 2008). Similar research has also been conducted in Europe.…”
Section: Evidence For Efficacy and Effectiveness: Influencing Dietmentioning
confidence: 99%